U-Th chronology and formation controls of methane-derived authigenic carbonates from the Hola trough seep area, northern Norway - Sauer, Simone; Cremiere, Antoine; Knies, Jochen; Lepland, Aivo; Sahy, Diana; Martma, Tonu; Noble, Stephen R.; Schonenberger, Jasmin; Klug, Martin; Schubert, Carsten J. (Chemical Geology, 2017)
We investigated methane-derived authigenic carbonate (MDAC) crusts and nodules from a cold seep site on the northern Norwegian continental shelf in ca. 220 m water depth to determine the timing and mode of their formation. Gas bubbling observed during remotely operated vehicle (ROV)-assisted sampling of MDAC crusts revealed ongoing seep activity. Authigenic carbonates were present as crusts on the seafloor and as centimetresize carbonate-cemented nodules at several intervals within an adjacent sediment core. Aragonite-dominated mineralogy of the MDAC crusts suggests formation close to the seafloor at higher rates of sulphate-dependent anaerobic oxidation of methane (AOM). In contrast, dolomite-cemented nodules are consistent with the formation at the sulphate-methane-transition zone deeper within the sediment at lower rates of AOM. The delta C-13-carbonate values of bulk rock and of micro-drilled aragonite samples vary between -22.2% and -34.6% (VPDB). We interpret the carbon in aragonite to be mainly derived from the anaerobic oxidation of thermogenic methane, with a minor contribution from seawater dissolved inorganic carbon (DIC). AOM activity is supported by high concentrations of AOM-related biomarkers of archaea (archaeol and 2-sn-hydroxyarchaeol) and sulphate-reducing bacteria (iso and anteiso-C-15:0 fatty acids) in the crusts. The dolomite nodules exhibit higher delta C-13-carbonate values (-12% VPDB) suggesting a smaller amount of methane-derived carbon, presumably due to the contribution of DIC migrating from depth, and lower AOM rates. The latter is supported by orders of magnitude lower concentrations of archaeol and sn-2-hydroxyarchaeol in the sediment interval containing the largest dolomite nodules. delta O-18 values of pure aragonite samples and dolomite nodules indicate the precipitation of carbonate close to isotopic equilibrium with seawater and no influence of gas hydrate-derived water. U-Th dating of two MDAC crusts shows that they formed between 1.61 +/- 0.02 and 4.39 +/- 1.63 ka BP and ...